Risk factors associated with malignancy in intraductal papillary mucinous neoplasia of the pancreas - Targarona, Javier (2025)
Objective: The objective of this study is to analyze the main clinical and epidemiological factors related to the risk of malignancy in intraductal papillary mucinous neoplasia of the pancreas in a cohort of patients seen at a referral clinic in Lima, Peru, based on the criteria of the IAP/Fukuoka guidelines. Materials and methods: This is a retrospective cohort study, which evaluated patients diagnosed with pancreatic IPMN from December 2015 to August 2023. They were classified according to involvement of the main branch, side branch, and mixed pancreatic ducts, considering aspects such as high-risk stigmata, concerning factors, age, sex, medical history, and others. Results: A total of 253 patients with pancreatic IPMN were included, 71.2% had side branch IPMNs, 9% had main branch IPMNs, and 19.8% were mixed. 49 patients (19.4%) underwent surgery at the time of diagnosis due to high-risk stigmata or factors concerning for malignancy. The remaining 204 patients were enrolled in a follow-up program for a mean of 31 months (6–100 months). During follow-up, a decision was made to operate on 38 of them. Of the 87 patients operated on, 36.7% presented invasive cancer and 11.4% high-grade dysplasia. The presence of a mural nodule greater than 5 mm increased the probability of malignancy 11.21 times; jaundice increased the risk of malignancy by more than 5 times. Wirsung duct dilation between 5 and 9.9 mm had a prevalence ratio (PR) of 2.12, and for dilation greater than 10 mm, a PR of 4.69 (p<0.05). The presence of three or more risk factors showed a PR of 6.77 in the bivariate analysis, and an adjusted prevalence ratio (aPR) of 17.11 in the multivariate analysis. Conclusion: Diagnosis and periodic monitoring of IPMNs allow for early detection of potentially malignant lesions, allowing for timely, often curative, surgery. However, there is currently no reliable way to diagnose and identify which cystic lesions already present or are likely to present malignant characteristics, thus providing clear indications for surgical intervention in these patients.